Household income and decentralized urban infrastructure : A case study of the integrated urban infrastructure development programme Yogyakarta urban development project - Baiquni, Muhammad (Yogyakarta:Fak. Geografi UGM, 1994)
Koleksi Referensi (Tidak Dipinjamkan)